Euro crash risk - Roman Kräussl; Thorsten Lehnert; Sigita Senulyte (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We identify crucial events during the European sovereign debt crisis and investigate their impact on the euro currency. In particular, we analyse how specific announcements related to vulnerable Eurozone member states, European Central Bank (ECB) actions, and credit rating downgrades affect the value and the crash risk of the euro. We proxy the value changes of the euro by its abnormal foreign exchange (FX) rate returns with respect to 35 currencies. The crash risk of the euro is proxied by the conditional skewness of the FX rate return distribution with respect to the same currencies. We find that the market reacts positively to news related to countries under the European and International Monetary Fund (IMF) rescue umbrella. We discover that ECB actions on average result in a euro depreciation on the day of the announcement reflecting obvious concerns of market participants, but the effect is partly corrected the day after. Our analysis also shows that sovereign credit rating downgrades tend to lead to a depreciation of the euro and, more importantly, to an increase of the euro crash risk. Interestingly, we find that specific announcements about Greece on average do not substantially affect the euro exchange rate directly, however, it does have an overall significant effect on the euro rash risk, imposing a substantial risk for the stability of the common currency in the Eurozone.
urn:nbn:de:hebis:30:3-386657
Keywords: G01; G14; 330; Sovereign debt crisis; News announcements; Euro value; Euro crash risk